Myeloid cell-derived apCAFs promote HNSCC progression by regulating proportion of CD4+ and CD8+ T cells - Feilong Ren; Lin Meng; Shize Zheng; Jiasen Cui; Shaoyi Song; Xing Li; Dandan Wang; Xing Li; Qilin Liu; Wenhuan Bu; Hongchen Sun (Journal of Experimental & Clinical Cancer Research)
Abstract It is well-known that cancer-associated fibroblasts (CAFs) are involved in the desmoplastic responses in Head and Neck Squamous Cell Carcinoma (HNSCC). CAFs are pivotal in the tumor microenvironment (TME) molding, and exert a profound influence on tumor development. The origin and roles of CAFs, however, are still unclear in the HNSCC, especially antigen-presenting cancer-associated fibroblasts (apCAFs). Our current study tried to explore the origin, mechanism, and function of the apCAFs in the HNSCC. Data from single-cell transcriptomics elucidated the presence of apCAFs in the HNSCC. Leveraging cell trajectory and Cellchat analysis along with robust lineage-tracing assays revealed that apCAFs were primarily derived from myeloid cells. This transdifferentiation was propelled by the macrophage migration inhibitory factor (MIF), which was secreted by tumor cells and activated the JAK/STAT3 signaling pathway. Analysis of the TCGA database has revealed that markers of apCAFs were inversely correlated with survival rates in patients with HNSCC. In vivo experiments have demonstrated that apCAFs could facilitate tumor progression. Furthermore, apCAFs could modulate ratio of CD4+ T cells/CD8+ T cells, such as higher ratio of CD4+ T cells/CD8+ T cells could promote tumor progression. Most importantly, data from in vivo assays revealed that inhibitors of MIF and p-STAT3 could significantly inhibit the OSCC growth. Therefore, our findings show potential innovative therapeutic approaches for the HNSCC. Significance: ApCAFs derived from myeloid cells promote the progression of HNSCC by increasing the ratio of CD4+/CD8+ cells, indicating potential novel targets to be used to treat the human HNSCC. Graphical Abstract